The private sector as the ‘unusual suspect’ in knowledge brokering for international sustainable development: a critical review - Kiwanuka, Suzanne N.; Cummings, Sarah; Regeer, Barbara (Knowledge Management for Development Journal, 2020)
Although the private sector’s engagement in sustainable international development is receiving increasing emphasis, its role in knowledge brokering has probably not yet received enough attention. Drawing on the Glegg and Hoens’ (2016) meta-framework of knowledge brokering we analysed the role of the private sector in knowledge brokering in Europe and Africa, based on the literature. Of the 702 records identified from 5 bibliographic databases, 13 studies, representing 44 case studies and two surveys were included. The private sector’s roles are versatile, extending beyond connecting research evidence to potential users, to connecting researchers to funding opportunities and to other researchers, and to hosting platforms for collaborative research and policy making. The private sector actively invests resources to facilitate knowledge uptake, however this is to a large extent driven by self-interest. Perceived self-interests remain a barrier to knowledge brokering with the private sector not always being a trusted partner. Our results demonstrate that ‘lobbying and advocacy’ should be an additional role included in the meta framework of knowledge brokering
Keywords: Private sector; Knowledge brokering; International development; Literature review; Africa; Europe